Sustainable Removal of Methylene Blue Using an Inverse-Vulcanized Polysulfide Derived from Waste Cooking Palm Oil - Abdullah Nayeem; Mohd Faizal Ali; Aishwarrya Narayanan; Jun Haslinda Shariffuddin (Bulletin of Chemical Reaction Engineering & Catalysis, 2026)
The environmental impact of waste palm cooking oil (WCO) has prompted extensive research into its potential applications, as it remains a significant pollutant, particularly in urban areas. This study investigates the synthesis of polysulfide using elemental sulfur and WCO as a sustainable method to repurpose these waste materials. The synthesized polysulfide showed effective methylene blue (MB) dye adsorption from wastewater, with adsorption performance assessed by varying the sulfur content (wt%) and dosage levels. Characterization techniques, including Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDS), were employed to analyze its structural and morphological properties. At the same time, UV-Vis spectrophotometry was used to measure the color removal efficiency. The highest removal rate of 78% was achieved at 70 wt% sulfur using 5 g of polysulfide in a 5 mg/L MB solution. The adsorption followed the Temkin adsorption isotherm (R2 = 0.96). Post-adsorption FTIR analysis confirmed that the degradation followed a physisorption mechanism, as no changes in functional bonds were observed. By simultaneously addressing WCO and sulfur waste, this study underscores the potential of polysulfide as an effective, sustainable adsorbent for wastewater treatment. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).